2011
DOI: 10.1001/archpediatrics.2011.142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Frequency, and Associations of Masturbation With Partnered Sexual Behaviors Among US Adolescents

Abstract: Participants: Nationally representative samples of adolescents aged 14 to 17 years. Main Outcome Measures: Solo masturbation, partnered sexual behaviors, and condom use. Results: Across age groups, more males (73.8%) reported masturbation than females (48.1%). Among males, masturbation occurrence increased with age: at age 14 years, 62.6% of males reported at least 1 prior occurrence, whereas 80% of 17-year-old males reported ever having masturbated. Recent masturbation also increased with age in males: 67.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 31 publications
3
44
1
4
Order By: Relevance
“…A similar association was found in a local study conducted in Selangor state and in an international study in the United States [16,33]. Masturbation is another sensitive issue to be discussed openly.…”
Section: Discussionsupporting
confidence: 79%
“…A similar association was found in a local study conducted in Selangor state and in an international study in the United States [16,33]. Masturbation is another sensitive issue to be discussed openly.…”
Section: Discussionsupporting
confidence: 79%
“…Retrospective studies suggest average ages of 13 and 15 years for men and women, respectively (Pinkerton, Bogart, Cecil, & Abramson, 2002). The prevalence of masturbation in the past three months increases with age among adolescent men: about 43% of 14 year olds report masturbation in the past 90 days compared to 67% of 17 year olds (Robbins et al, 2011). In contrast, the percentages of 14 and 17 year old women reporting masturbation in the past 90 days are quite similar at about 36% for both ages (Robbins et al, 2011).…”
Section: Linking Adolescent and Adult Sexualitymentioning
confidence: 99%
“…The prevalence of masturbation in the past three months increases with age among adolescent men: about 43% of 14 year olds report masturbation in the past 90 days compared to 67% of 17 year olds (Robbins et al, 2011). In contrast, the percentages of 14 and 17 year old women reporting masturbation in the past 90 days are quite similar at about 36% for both ages (Robbins et al, 2011). Lifetime prevalence of masturbation, however, continues to increase into young adulthood, with prevalence highest among those aged 25–34 (Gerressu, Mercer, Graham, Wellings, & Johnson, 2008).…”
Section: Linking Adolescent and Adult Sexualitymentioning
confidence: 99%
“…A study of US adolescents aged between 14 and 17 years found the prevalence of masturbation was higher among males (Robbins, 2011). Based on results of a meta-analysis from 177 sources, males aged over 18 years showed more positive attitudes towards masturbation than females, whereas females aged below 18 had more positive attitudes than males under 18 (Oliver & Hyde, 1993).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%